If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 89 + -2x = 3x + 24 Reorder the terms: 89 + -2x = 24 + 3x Solving 89 + -2x = 24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 89 + -2x + -3x = 24 + 3x + -3x Combine like terms: -2x + -3x = -5x 89 + -5x = 24 + 3x + -3x Combine like terms: 3x + -3x = 0 89 + -5x = 24 + 0 89 + -5x = 24 Add '-89' to each side of the equation. 89 + -89 + -5x = 24 + -89 Combine like terms: 89 + -89 = 0 0 + -5x = 24 + -89 -5x = 24 + -89 Combine like terms: 24 + -89 = -65 -5x = -65 Divide each side by '-5'. x = 13 Simplifying x = 13
| 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 | | 4r+6=22 | | e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x | | 5x+13=-39-8x | | 114-2x=9x+18 | | 4x+7y=299 | | 16x-8=6x+42 | | 13x+13=76-4x | | 34-g=25 | | 18x-9=6x+42 | | 9-9x=144-44x | | 2x+38=10x-26 | | -72-10x=9x+18 |